Pengaruh Self-Esteem dan Dukungan Sosial Guru terhadap Optimisme Orang Tua yang Memiliki Anak Berkebutuhan Khusus yang di Mediasi dengan Self-Efficacy Orang Tua (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Parenting for children with special needs (ABK) often poses significant emotional challenges for parents, so optimism is an important aspect in maintaining mental health and the sustainability of parenting. This study aims to analyze the influence of self-esteem and social support of teachers on the optimism of parents with disabilities, with self-efficacy as a mediating variable. The method used is quantitative with a causality approach, involving parents of crew members at SLB Swadaya Semarang. Data collection was carried out through a structured questionnaire, and data analysis using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study show that self-esteem has a positive and significant influence on parental optimism through increased self-efficacy. In contrast, teachers' social support did not show a significant influence on optimism, either directly or through self-efficacy mediation. These findings indicate that strengthening self-esteem and self-efficacy in ABK parents is an important strategy in building an optimistic attitude in parenting. Meanwhile, the role of teachers remains relevant as a provider of moral support and a facilitator of positive relationships between schools and families. This study recommends psychosocial interventions that focus on increasing parental self-esteem and self-efficacy as an effort to strengthen emotional resilience in the care of children with special needs.